Biomarkers for patients with Wilms tumor: a review - Zheng, Hongfeng; Liu, Jiangui; Pan, Xiuwu; Cui, Xingang (Frontiers in Oncology, 2023)
Wilms tumor, originating from aberrant fetal nephrogenesis, is the most common renal malignancy in childhood. The overall survival of children is approximately 90%. Although existing risk-stratification systems are helpful in identifying patients with poor prognosis, the recurrence rate of Wilms tumors remains as high as 15%. To resolve this clinical problem, diverse studies on the occurrence and progression of the disease have been conducted, and the results are encouraging. A series of molecular biomarkers have been identified with further studies on the mechanism of tumorigenesis. Some of these show prognostic value and have been introduced into clinical practice. Identification of these biomarkers can supplement the existing risk-stratification systems. In the future, more biomarkers will be discovered, and more studies are required to validate their roles in improving the detection rate of occurrence or recurrence of Wilms tumor and to enhance clinical outcomes.